Pembuatan Alat Pengering Tangan Otomatis Untuk Pencegahan Penyebaran Virus Covid 19 - Idham A Djufri; Ahmad P Sardju (Universitas Khairun, 2021)
Socialization about hand washing using hand sanitizer is an effort to prevent the early spread of the covid-19 virus which is very unusually fast transmission. This automatic hand dryer is one of the supporting equipment when we finish washing our hands in public places that have been provided by handwashing / sink. Community service is done so that the community can easily dry their hands after washing their hands in the place that has been provided, in addition to maintaining the cleanliness of the environment from used tissue hand dryers that are often discarded out of place. The implementation of this service is carried out in several stages in order to obtain maximum results and complete reporting.